Assessment of the economic viability, environmental, and social impacts of green hydrogen production: an Algerian case study - Anim-Mensah, Alexander; Drouiche, Nadjib; Boulaiche, Wassila (Frontiers in Membrane Science and Technology, 2024)
The impacts of climate change are real and in many parts of the world testify to its harsh reality, including rampant extreme weather events, droughts, heat, wildfires, and flooding which have recorded in places which have not experienced them in recent memory. In the quest to avert such events, there is a growing awareness and demand for sustainable processes and operations. Today, sustainability encompasses a balance between ecological footprint and human development index, taking into consideration economics, the green environment, safety, quality, ethics, diversity and inclusion (D&I), and communities. This article presents some steps that have been taken by Algeria to balance energetic autonomy and sustainable development, and a case study on green hydrogen production employing membrane processes. Algeria’s objective to join the global fight against climate change is to develop its green hydrogen base. Given its resources, including available solar and wind power, seawater desalination plants, building capacity, and its favorable location, it is developing its green hydrogen economy to supply hydrogen, especially to Europe. This presents an opportunity for other developing nations, especially in Africa, to gain from this experience.